2017
DOI: 10.1016/j.redox.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione inhibits antibody and complement-mediated immunologic cell injury via multiple mechanisms

Abstract: Antioxidant glutathione (GSH) plays an important role in the regulation of immunity. However, little is known about its effects on humoral immunity, especially its action on effector molecules like antibody and complement. Given that these molecules contain abundant disulfide bonds, we speculated that GSH might influence the action of these proteins via its thiol function. Using a model of a glomerular mesangial cell (MC) lysis induced by antibodies plus complement, we addressed this hypothesis. Exposure of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Our study and chart review showed that evaluating patients for associated environmental toxicity and using detoxification with glutathione (GSH) is clinically useful, especially during Herxheimer reactions. Glutathione modulates inflammation [172,173]. A 2018 PNAS report found that intracellular GSH production was increased up to 10-fold during an infection with Borrelia burgdorferi , and infection was a key factor in inflammation/cytokine production [174].…”
Section: Discussionmentioning
confidence: 99%
“…Our study and chart review showed that evaluating patients for associated environmental toxicity and using detoxification with glutathione (GSH) is clinically useful, especially during Herxheimer reactions. Glutathione modulates inflammation [172,173]. A 2018 PNAS report found that intracellular GSH production was increased up to 10-fold during an infection with Borrelia burgdorferi , and infection was a key factor in inflammation/cytokine production [174].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when GSH levels were restored with N-acetycysteine (NAC), a precursor of L-cysteine, supplementation, T cell proliferation and IL-2 levels were increased. More recently, it has been suggested that GSH supplementation may protect cells from immunological cell damage by inhibiting the complement activation cascade and the binding of antibodies to antigens in isolated glomerular mesangial cells from rats, suggesting the possible use of GSH in the treatment of certain immune disorders [ 99 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…However, GSH is the main antioxidant in the body and studies have underlined that GSH depletion is involved in a number of pathologies . GSH decrease is certainly involved in oxidative damage and risk factors for cardiovascular disease , inflammatory reactions , cognitive processes , and immunity . The observation that NAC at therapeutic doses counteracts the deleterious effect of APAP on whole blood GSH concentration in healthy volunteers suggests that this depletion could be prevented by adequate sulfur amino acids intake such as methionine, cysteine , or NAC for the biosynthesis of GSH, especially in vulnerable persons.…”
Section: Discussionmentioning
confidence: 99%